2017
DOI: 10.1002/da.22618
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of interventions for posttraumatic stress disorder and depression in adult survivors of mass violence in low- and middle-income countries

Abstract: Our findings suggest that psychological interventions can effectively reduce symptoms of PTSD and depression in LMICs. Future research needs to focus on cost-effective interventions that are likely to be disseminated to the large numbers of war survivors in LMICs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 66 publications
0
51
1
Order By: Relevance
“…In addition, more research is needed to investigate the efficacy of existing psychological interventions for depression in civilian war survivors, especially in LMICs (Bolton et al, 2003;Morina, Malek, Nickerson, & Bryant, 2017b). A recent systematic review of randomized controlled trials (RCTs) on depression and PTSD among adult survivors of mass violence in LMICs concluded that in the18 RCTs conducted in this population, only one trial had treatment of depression as the main focus whereas PTSD was the main treatment focus in nine trials (Morina et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more research is needed to investigate the efficacy of existing psychological interventions for depression in civilian war survivors, especially in LMICs (Bolton et al, 2003;Morina, Malek, Nickerson, & Bryant, 2017b). A recent systematic review of randomized controlled trials (RCTs) on depression and PTSD among adult survivors of mass violence in LMICs concluded that in the18 RCTs conducted in this population, only one trial had treatment of depression as the main focus whereas PTSD was the main treatment focus in nine trials (Morina et al, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Although interventions that are effective in high-resource settings have also been shown to be effective in low-resource settings and for migrant populations (Morina, Malek, Nickerson, & Bryant, 2017), cultural adaptation of the original intervention protocols to the local culture is essential. During cultural adaptation, the intervention protocol is systematically modified considering language, culture, and context compatible with the client’s cultural meanings and values.…”
Section: Evidence-based Interventions For Refugeesmentioning
confidence: 99%
“…NET is one of the few PTSD interventions that has been developed for and extensively tested with populations exposed to multiple traumatic events, particularly in post-conflict settings (Gwozdziewycz & Mehl-Madrona, 2013). Past research suggests that NET and several other trauma-focused CBT interventions are effective in reducing PTSD (and comorbid depression) in survivors of mass violence in low-and middle-income countries (Morina, Malek, Nickerson, & Bryant, 2017;Nickerson et al, 2011).…”
Section: Collaborating Authorshipmentioning
confidence: 99%